Visual impairment, Creativity and Education - Prado, Jose Enrique Llamazares de; Gago, Ana Rosa Arias; Alvarez, Maria Antonia Melcon (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
In the following work arises the importance in the education of key elements such as creativity and divergent thinking. This article has as main objective the review of the studies of visual disability and creativity. This study aims to a systematic reflection of the synthetic quantitative estimate of all of the available studies, posing a theoretical framework linking creativity in the education of students with visual impairment, providing personal assessments. Inside the findings evidenced the function of the creative potential, through divergent thinking in the creation of concepts and ideas, solving problems, with interest not only in education but in any area of life.